Letramento científico e habilidades didáticas em produções escritas de professores de ciências - GOMES, Ana Silvia Alves (Universidade Federal do Pará, 2022)
This research aimed to identify, describe, and point out possible correlations between levels of scientific literacy and teaching skills of elementary school teachers. This is exploratory qualitative-quantitative research, where the MAXQDA 2020 and JAMOVI 2.2.5 software were used to produce content analysis and descriptive statistics of collected data, together with a group of 18 (eighteen) teachers from basic education, freshmen of a stricto sensu postgraduate course, who voluntarily answered questions from the so-called Scientific Literacy Skills Test (TOSLS) and prepared, in writing, proposals for didactic sequences. To analyze these proposals, a Didactic Skills Analysis Protocol (PAHD) was created, whose analysis categories were inspired by the ideas of contemporary constructivist authors. The analysis of the results of the categorization of didactic skills evidence showed that the participants presented, on average, half of the didactic skills of a constructivist nature proposed in the PAHD. On average, participants in this study also did not perform well on the TOSLS. The data obtained were not sufficient to support the hypothesis of correlation between Scientific Literacy and Teaching Skills. However, it is not possible to rule out the possibility of observing the occurrence of statistically significant correlations between such abilities in sufficiently larger and more diversified samples. The results suggest that, if one is interested in implementing curricular guidelines and teaching-learning-assessment strategies of a constructivist nature in schools, it is necessary to increase teacher training programs with objectives, themes and teaching strategies focused on skills that had a low incidence. in this study, since, as discussed in the text, all of them are essential for planning and conducting classes of a constructivist nature and important for the professional development of teachers. Although there is still much to be explored on the issue of didactic skills, the scope of this thesis, and particularly the PAHD, had great potential as an instrument for research and professional development. Despite the limitations pointed out, the results and scope of this thesis constitute an important reference both for future research and for eventual reformulations in science teacher training programs, in view of the empirical results, the theoretical discussions and the methodological ideas it contains.